Once upon a time in the veld: South Africa westerns in context - Lapa Petit, Andre Ricardo (Centre for Film and Media Studies, 2020)
Historically westerns have been one of the most popular film genres in South Africa but very few features have been produced locally. In addition, the few productions that exist have not received significant attention from researchers and scholars. Thus, this study aims to contribute to South African film research by contextualizing the origin, content and distribution of western genre films conceived and produced by South African filmmakers and companies. It does so by exploring two avenues of inquiry that are intrinsically connected. First, by establishing these films' historical background in relation to the development of the South African film industry and the evolution of the western genre as a whole; and second, by determining how, or if South African ideology and culture have influenced the narrative and aesthetic structure of such films by comparison and contrast with established conventions of the genre's corpus. The study ultimately argues that, despite their popularity westerns have not been a major influence in the development of the South African film industry due to nationalist and ideological discourses that stifled the genre's growth in country, relegating it to a marginal position. The study also concludes that the narrative and aesthetic structure of all South African westerns reveal larger socio-political trends at work during their inception. In this way they function as indirect chronicles of the country's history and its relation to the world, alluding to cultural norms, popular beliefs and governmental mindsets. As such, their importance lies not in their outstanding contributions to the canon of South African production, but instead as examples of experiments in the negotiation and adaptation of national ideology, or a critique of it, utilizing cinematographic tropes.